Implementation of Differentiated Learning to Improve The Results of Football Shooting Techniques In The Learning of Physical and Sports Courses of Grade X Flores Students of State High School 1 Palopo - Muhammad Ramadhan Astaman; Fahrizal Fahrizal; Muh. Adnan Hudain; Ramli Ramli; Juhanis Juhanis (UNIVERSITAS NEGERI MAKASSAR, 2024)
The purpose of this study was to determine the ability of students' football shooting techniques and how to improve the material of basic football techniques by using differentiated learning. This type of research is Classroom Action Research. The instruments used are 1) a Learning style test, and 2) a Football shooting technique test. The research design uses the Kemmis & McTaggart model. The implementation of the action includes four steps, namely: 1) Planning, 2) Implementation of Action (Action), 3) Observation, and 4) Reflection. Based on the results of research at the pre-cycle stage, the results of the learning style of students with an average of students with a kinesthetic learning style of 66.3 or 24 students, a visual learning style with a percentage of 25% or 9 students, and an auditory learning style with a percentage of 8.3% or 3 students. The percentage of the results of the assessment of football shooting techniques cycle 1 with an average student score of 74 with 42% completeness. Then in cycle II, it increased with an average student score of 86%. So it can be concluded that the application of differentiated learning can improve the results of students' football shooting techniques.